Psalm 91 and its wisdom connections - Botha, Phil J. (Old Testament Essays, 2012)
The paper investigates the literary and theological provenance of Ps 91. It is shown that Ps 91 (in its present form) was composed by someone who had access to Proverbs, in particular Prov 3, while Ps 91 itself played a role in the composition of Job 5:17-26. As part of the "triptych" formed by Pss 90, 91 and 92, the psalm was intended to strengthen the conviction of its author that Yahweh is able and willing to provide protection to the individual believer who attaches himself or herself wholeheartedly to his or her God, saving the true and wise believer.
free